The modulation of potassium channels by estrogens facilitates neuroprotection - Li, Xian-Tao (Frontiers in Cell and Developmental Biology, 2022)
Estrogens, the sex hormones, have the potential to govern multiple cellular functions, such as proliferation, apoptosis, differentiation, and homeostasis, and to exert numerous beneficial influences for the cardiovascular system, nervous system, and bones in genomic and/or non-genomic ways. Converging evidence indicates that estrogens serve a crucial role in counteracting neurodegeneration and ischemic injury; they are thereby being considered as a potent neuroprotectant for preventing neurological diseases such as Alzheimer’s disease and stroke. The underlying mechanism of neuroprotective effects conferred by estrogens is thought to be complex and multifactorial, and it remains obscure. It is well established that the K+ channels broadly expressed in a variety of neural subtypes determine the essential physiological features of neuronal excitability, and dysfunction of these channels is closely associated with diverse brain deficits, such as ataxia and epilepsy. A growing body of evidence supports a neuroprotective role of K+ channels in malfunctions of nervous tissues, with the channels even being a therapeutic target in clinical trials. As multitarget steroid hormones, estrogens also regulate the activity of distinct K+ channels to generate varying biological actions, and accumulated data delineate that some aspects of estrogen-mediated neuroprotection may arise from the impact on multiple K+ channels, including Kv, BK, KATP, and K2P channels. The response of these K+ channels after acute or chronic exposure to estrogens may oppose pathological abnormality in nervous cells, which serves to extend our understanding of these phenomena.